Aflasafe product GH01 and GH02 for Ghana - CGIAR Research Program on Agriculture for Nutrition and Health (2017)
Aflasafe GH01 and Aflasafe GH02 two biocontrol products developed for use in maize and groundnut in Ghana, have been approved by the regulatory authority Ghana Environmental Protection Agency in 2018. Now both product are available for commercial use. The product is commercialized by the company MacroFertil